Post-traumatic instability of the first metatarsophalangeal joint: a novel surgical technique of capsular reconstruction in a young kickboxer - Gianni Caizzi; Michele Coviello; Andrea Franchini; Flavia Riefoli; Florianna Palmiotto; Biagio Moretti (Medicinski glasnik, 2022)
Aim: To report a novel surgical technique of capsular reconstruction of post-traumatic instability of the first metatarsophalangeal joint (MTPJ). Methods: The clinical case is related to a 24-year-old male athlete whose clinical symptoms began with pain and spontaneous dislocation of the left first MTPJ during a kickboxing fight. He received conservative treatment (cryotherapy and rest) at first. Afterwards, he referred persistent hallux instability associated with moderate pain, despite normal anatomic alignment with no evidence of first ray deformity. Plain traditional x-rays of the left foot, magnetic resonance imaging (MRI), static and dynamic ultrasonography (US) and clinical tests were performed in order to diagnose capsular ligamentous structure lesions. Results: The plain x-rays showed hallux abductus angle of 3°. The MRI and US demonstrated a rupture of the lateral capsular ligamentous structures and detachment of the abductor tendon. The pull out medium-lateral of the capsule with the abductor suture was performed as a treatment for dynamic hallux varus deformity. At six-month follow up, the patient walked without lameness with complete active and passive range of motion and with a stable first MTPJ. Conclusion: The patient presented with the post traumatic instability of the first metatarsophalangeal joint treated with a novel surgical technique of capsular reconstruction. The patient returned to the full weight-bearing in only 2 months of rehab. To the best of our knowledge, the surgical correction proposed has not been previously described.
Keywords: hallux varus; joint instability; metatarsophalangeal joint